1992
DOI: 10.1088/0954-3899/18/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Description of the ov beta beta decay of48Ca,76Ge,100Mo,128,130Te

Abstract: 1W, 128 and 130 systems is examined in the context of the QRPA formalism without invoking the closure approximation. All possible nuclear matrix elements are calculated including the nucleon recoil contributions as well as those resulting from the exchange of heavy intermediate Majorana neutrinos. Using the hest presently available experimental limit TEP(Ov) > 1.1 x 1@' y the following limits on the lepton violating parameters are extracted: I(my)l<2.0eV. (1/M,)p126.7X 10'GeV. As3.3XlO-" and n s 4 . 2 ~ 10-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The short-range correlations between the two interacting nucleons are now taken into account by a correlation function [5,10].…”
Section: νmentioning
confidence: 99%
“…The short-range correlations between the two interacting nucleons are now taken into account by a correlation function [5,10].…”
Section: νmentioning
confidence: 99%
“…The calculation of the 0νββ-decay matrix elements is based on some approximation schemes, from which the Quasiparticle Random Phase Approximation (QRPA) is the most prominent one [5]- [8], despite an uncertainty in the calculation of the nuclear matrix element, which is related to its sensitivity on the renormalization of the particle-particle component of the residual interaction. Thus in the framework of proton-neutron QRPA (pn-QRPA) using the zero range delta-force Engel et al [6] have found a strong suppression of the 0νββ-decay matrix elements by introducing short-range correlations, whereas Tomoda et al [5] and Muto et al [7] by using a more realistic effective NN interaction arrived at the opposite conclusion.…”
mentioning
confidence: 99%
“…Here, R = r 0 A 1/3 is the nuclear radius (r 0 = 1.1 fm) and the parameter Λ of the dipole shape nucleon form factor is chosen to be 0.85 GeV [8,10]. In the full-RQRPA for the matrix elements of the one-body transition densities we obtain…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, following the work of Vogel and Zirnbauer [1], the proton-neutron (pn) quasiparticle random phase approximation (QRPA) has turned out to be the most popular model for calculating the nuclear wave functions involved in the ββ-transitions [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. The QRPA calculations have shown that the ground state correlations (GSC), induced by the residual pn interaction in the particle-particle (PP) channel, play an essential role in quenching the ββ 2ν decay probabilities.…”
Section: Introductionmentioning
confidence: 99%